Investigation of The Effects of Solution Heat Treatment (SHT) on Microstructure, Phase Transformation, and Corrosion Properties of AlSi10Mg Alloy Produced by LPBF - Yılmaz, Mustafa Safa; Tütük, İbrahim; Ural, Mehmet Moğoltay; Özer, Gökhan (Emerald, 2025)
Purpose – This study aims to apply solution heat treatment (SHT) to AlSi10Mg material produced by laser powder bed fusion (LPBF) technique at lower temperatures and times instead of the conventional T6 heat treatment (540°C/2 h). Design/methodology/approach – The effects of these heat treatments on the microstructure, phase transformation and corrosion properties of the material were investigated. Optical microscope, Smartzoom5 device (with Zen Core 3.5 program), scanning electron microscopy (SEM), focused ion beam SEM (FIB-SEM) and Energy dispersive X-ray analysis techniques were used to examine the microstructural properties, and X-ray diffractometry (XRD) techniques were used to determine the phase analysis. Potentiodynamic polarization and electrochemical impedance spectroscopy techniques were used for corrosion measurements. Findings – The results were compared with conventional T6 heat treatments, revealing that the developed alternative dissolution heat treatments showed better corrosion resistance than the traditional T6 heat treatment. Originality/value – This study presents a new alternative to the traditional T6 heat treatment with SHT, which is performed over a long time and temperature, and a new alternative to heat treatment at a shorter time and temperature. These findings are of significant industrial importance because AlSi10Mg alloys are used in critical areas today.
Keywords: AlSi10Mg; Electrochemical Corrosion; Additive manufacturing (AM); New T6 heat treatment (NT6); Powder bed laser fusion (PBLF)